How to know if it's time to go : a 10-step reality test for your marriage - Birnbach, Lawrence, 1944-; Hyman, Beverly (New York : Sterling Ethos, 2010)
'Provides ten steps to help you examine how serious the problems are in your marriage, what you might try to do to improve it, and, if that's not possible, whether it's time to get serious about divorce'--Cover.
Includes bibliographical references (p. 195-202) and index.
Keywords: Marriage; Marriage -- Psychological aspects; Divorce